Deconstructing Apathy in Parkinson's Disease: Challenges in Isolating Core Components of Apathy From Depression, Anxiety, and Fatigue - Ineichen, Christian; Baumann-Vogel, Heide (Frontiers in Neurology, 2021)
Apathy, fatigue and depression are amongst the most debilitating non-motor syndromes of Parkinson’s disease (PD). The aim of this study was to examine the prevalence of apathy, depression, anxiety and fatigue and whether these syndromes are separable in PD. A total of 337 patients were examined using the Unified Parkinson’s Disease Rating Scale (UPDRS part III), the Apathy Evaluation Scale, the Hospital Anxiety and Depression Scale and the Fatigue Severity Scale. Using standard cutoff criteria, the prevalence rates of significant apathy, mild-to-severe depression, mild-to-severe anxiety and severe fatigue were 23,7%, 13.4%, 15.4% and 17.8%, respectively. Next, confirmatory factor analysis was employed of items from these three clinical scales. A priori hypothesis testing including four different factors (reduced motivation/interest, physical fatigue, reduced pleasure, anxiety) was performed. The factor analysis revealed strong fit statistics for the model with χ2 (57, N = 377) = 58.9, p = 0.41, CMIN/DF = 1,034, NFI = .977, CFI = .999, IFI = .999, RFI = .968 and TLI = .999. The RMSEA was .01, and the standardized RMR was 0.027. These results support the hypothesis that apathy, fatigue, depression and anxiety represent prevalent syndromes that can be separated in Parkinson’s disease and that apathy is not just a subcomponent of depression or fatigue. The results of this study may contribute to a clearer diagnostic process for apathy, fatigue and depression and may aid in patient care.